The Medical Basis of Psychiatry - Fatemi, S. Hossein; Clayton, Paula J. (Humana Press : Imprint: Humana, 2008)
Psychiatry has emerged as a burgeoning scientific field with major advances in etiology and treatment of several disorders. Just as there was excitement in the anatomic advances that took place a hundred years ago when Emil Kraepelin and his collaborators took on the enormous task of classification of psychiatric disorders based on rational scientific thinking, new advances in genetics, biochemistry, neuroanatomy and pharmacotherapy of mental disorders have brought us even closer to a better understanding of complex disorders like schizophrenia, bipolar disorder, depression and even autism. The major goal of the previous edition of this classic book was to update the busy clinician, psychiatric resident and medical student with the most up-to-date information on etiology, diagnosis and treatment of psychiatric disorders. This goal remains the focus of the third edition of this book. In this updated and expanded edition, the reader is provided with the most contemporary information and literature supported by a close survey of the field. Several new chapters dealing with new concepts in biology and treatment of mental disorders have been added. This new edition of this classic title, with its focus on biologic and medical aspects of psychiatry, will continue to be of significant help to all interested in the scientific practice of psychiatry.